Development of a Web-Based Accreditation System for Study Program Management using the Waterfall Model - Taufiqurrahman; Junaedy; Syarifuddin, Rizal (Nusantara Journal of Artificial Intelligence and Information Systems, 2025)
At Universitas Islam Makassar, study program accreditation is still managed manually. This slows down the process, increases the workload, and makes errors more likely. This research introduces a web-based accreditation system designed to simplify document submission, verification, and assessment. The system was developed using the Waterfall model, moving through requirement analysis, design, implementation, testing, and maintenance. Three user roles were defined: administrator, head of study program, and assessor, each with tailored access and features. Functions include structured document uploads, real-time accreditation tracking, and role-based dashboards. The system was tested using black-box testing, and all key features worked as intended. Results show the system improves process speed, reduces manual work, and helps stakeholders manage accreditation more efficiently. Further features like video uploads and automated notifications are planned for future updates.